I'm having serious problems whenever I try to convert a formula to CNF/DNF. I can do it with easier formulas, but this one I just can't understand for some reason:
I've tried removing the → operators and replacing them with other formulas, after that I've tried to apply De Morgan's laws to it, etc, like this:
1. ¬A∨B∨¬(A∧¬B→B∧¬C) 2. ¬A∨B∨¬((B∧¬C)∨¬(A∧¬B)) 3. ¬A∨B∨(¬(B∧¬C)∧¬¬(A∧¬B)) 4. ¬A∨B∨((¬B∨¬¬C)∧(A∧¬B)) 5. ¬A∨B∨((¬B∨C)∧(A∧¬B))
I'm not sure if I even did one correctly, not the mention all of it, and I'm also stuck here, so I don't know how to continue..
I'd really appreciate if someone could help me solve this! Thanks!